Screening of magnetic fields by superconducting and hybrid shields with a circular cross-section. (1st April 2022) - Gozzelino, Laura; Fracasso, Michela; Solovyov, Mykola; Gömöry, Fedor; Napolitano, Andrea; Gerbaldo, Roberto; Ghigo, Gianluca; Laviano, Francesco; Torsello, Daniele; Grigoroscuta, Mihai A; Aldica, Gheorghe; Burdusel, Mihail; et al.
Abstract: The use of superconducting (SC) materials is crucial for shielding quasi-static magnetic fields. However, the need for space-saving solutions with high shielding performance requires the development of a three-dimensional (3D) modelling procedure capable of predicting the screening properties for different orientations of the applied field. In this paper, we use a 3D numerical model based on a vector potential formulation to investigate the shielding ability of SC screens with cylindrical symmetry and a height/diameter aspect ratio close to unity, without and with the superimposition of a ferromagnetic (FM) circular shell. The chosen materials were MgB2 and soft iron. First, the outcomes of the calculations were compared with the experimental data obtained with different shielding arrangements, achieving a notable agreement in both axial field (AF) and transverse field (TF) orientations. Then, we used this validated modelling approach to investigate how the magnetic mitigation properties of a cup-shaped SC bulk can be improved by the superimposition of a coaxial FM cup. Calculations highlighted that the FM addition is very efficient in enhancing the shielding factors (SFs) in the TF orientation. Assuming a working temperature of 30 K and using a layout with the FM cup protruding over the SC one, SFs up to eight times greater than those with a single SC cup were attained at applied field up to 0.15 T, reaching values equal to or higher than 10 2 in the inner half of the shield. In the AF orientation, the addition of the same FM cup incurs a modest worsening at low fields, but at the same time it widens the applied field range where SF ⩾ 10 4 occurs near the close extremity of the shield to over 1 T.